Factors Affecting Delivery Performance of Pamarican District Farmers' Unhulled Rice Grain Supply Chain System of Ciamis Regency with PT Mitra Desa Pamarican - Octaviana Helbawanti; Dwi Apriyani (Universitas Muhammadiyah Malang, 2022)
One of the problems in fulfilling the staple food consumption of rice in Indonesia is the rice distribution system. Delivery performance is one of the important measurements in the supply chain system since it is an indicator of the accuracy of the quantity and time of grain delivery from rice farmers involved in partnership with PT MDP. Respondents used in this study consisted of 30 rice farmers chosen through purposive sampling technique in Pamarican District, Ciamis Regency, West Java. The analytical method used is multiple linear regression or multiple linear regression model with Ordinary Least Square to analyze the influence of the distance of the farmer to the grain collection point, the length of time the farmer makes inventory, the experience of farming, the farmer's storage capacity, and the method of payment for grain or the transaction system on the delivery performance. The results of the analysis show the variables of distance, inventory, and transaction systems. The distance variable has a significant positive effect, the inventory variable has a significant negative effect, and the cash transaction system will improve the delivery performance of farmers to PT MDP. Farmers make cost efficiency for grain delivery by collecting grain first. A decrease in delivery performance occurs when farmers store the grain longer